The Growth of Botryococcus braunii Microalgae as a Lipid Producer in a Mixed Medium of Coconut Water and Seawater - Saputro, Bintoro Rudi; Kusdiyantini, Endang; Kusumaningrum, Hermin Pancasakti (JURNAL SAINS DAN MATEMATIKA, 2015)
Energy needs in fuel sector tend to increase for supporting human life. Green microalgae (Chlorophyceae) can be used as an alternative solutions for bioenergy. Botryococcus braunii is lipid producer microalgae which can be processed further into biodiesel. Microalgae growth medium such as Walne can be substituted with coconut water that reducing economical cost. This research aims to determine the growth of B. braunii using coconut water and its effect on lipid production. The experiment conducted into five treatments of coconut water consist of P0 (0%), P1 (10%), P2 (7.5%), P3 (5%), and P4 (2.5%) for five days incubation and three repetitive step. Microalgae growth was calculated according to cell count using hemocytometer. The results showed that 2.5% coconut water substitution exhibited the best growth rate and lipid production, i.e. the amount of 547 cells / ml and produced lipid level according to these treatment increased 179% comparing with control.